Study on the Key Technologies of Mobile Application Development - Yingqi Wei; Weiping Lin; Shaolong Yang (Dianxin kexue)
With the widespread of 3G smartphone，mobilephone acts not only as communication tool，but also as life partners. As assistants，mobile applications make life very different. In terms of application characteristics， development model and business model，discrepancy is significant between the patterns of mobile applications and desktop applications. By studying the key characteristics of mobile internet applications，the agile development of mobile and the tendency of technologies，the recipes of successful mobile development were analyzed.